Compassion-Focused Technologies: Reflections and Future Directions - Day, Jamin; Finkelstein, Joel C.; Field, Brent A.; Matthews, Benjamin; Kirby, James N.; Doty, James R. (Frontiers in Psychology, 2021)
Compassion is a prosocial motivation that is critical to the development and survival of the human species. Cultivating compassion involves developing deep wisdom, insight and understanding into the nature and causes of human suffering; and wisdom and commitment to take positive action to alleviate suffering. This perspective piece discusses how compassion relates to the context of modern technology, which has developed at a rapid pace in recent decades. While advances in digital technology build on humankind’s vast capacity to develop practical tools that promise to enrich our lives and improve our social connections, in reality the effects are often far from benign. The motives underlying the development of many contemporary digital platforms seem rooted in competitiveness and capitalism; while modern social media and online platforms are having a profound and pervasive impact on the mental health and wellbeing of humans around the globe. Nonetheless, digital technology holds considerable potential to promote compassionate insight, wisdom and prosocial behaviour. We reflect on the current state of technology within human society and examine the notion of compassionate technologies; discuss how contemporary paradigm shifts such as the inclusive design movement may be harnessed to build tools and platforms that promote collective good and increase prosocial behaviour; and highlight examples of initiatives that are harnessing modern technology to advance democracy, collective knowledge, and personal freedoms and agency.